HIV Non-Nucleoside Reverse Transcriptase Inhibitor Efavirenz Reduces Neural Stem Cell Proliferation in Vitro and in Vivo. Issue 11 (November 2016) - Jin, Jingji; Grimmig, Bethany; Izzo, James; Brown, Lecia A. M.; Hudson, Charles; Smith, Adam J.; Tan, Jun; Bickford, Paula C.; Giunta, Brian
The prevalence of HIV-associated neurocognitive disorders (HAND) remains high despite combination antiretroviral therapy (cART). There is evidence that neural stem cells (NSCs) can migrate to sites of brain injury such as those caused by inflammation and oxidative stress, which are pathological features of HAND. Thus, reductions in NSCs may contribute to HAND pathogenesis. Since the HIV non-nucleoside reverse transcriptase inhibitor efavirenz (EFV) has previously been associated with cognitive deficits and promotion of oxidative stress pathways, we examined its effect on NSCs in vitro as well as in C57BL/6J mice. Here we report that EFV induced a decrease in NSC proliferation in vitro as indicated by MTT assay, as well as BrdU and nestin immunocytochemistry. In addition, EFV decreased intracellular NSC adenosine triphosphate (ATP) stores and NSC mitochondrial membrane potential (MMP). Further, we found that EFV promoted increased lactate dehydrogenase (LDH) release, activation of p38 mitogen-activated protein kinase (MAPK), and increased Bax expression in cultured NSCs. Moreover, EFV reduced the quantity of proliferating NSCs in the subventricular zone (SVZ) of C57BL/6J mice as suggested by BrdU, and increased apoptosis as measured by active caspase-3 immunohistochemistry. If these in vitro and in vivo models translate to the clinical syndrome, then a pharmacological or cell-based therapy aimed at opposing EFV-mediated reductions in NSC proliferation may be beneficial to prevent or treat HAND in patients receiving EFV.